A Critical Review of Microelectrode Arrays and Strategies for Improving Neural Interfaces. Issue 19 (28th August 2019) - Ferguson, Morgan; Sharma, Dhavan; Ross, David; Zhao, Feng
Abstract: Though neural interface systems (NISs) can provide a potential solution for mitigating the effects of limb loss and central nervous system damage, the microelectrode array (MEA) component of NISs remains a significant limiting factor to their widespread clinical applications. Several strategies can be applied to MEA designs to increase their biocompatibility. Herein, an overview of NISs and their applications is provided, along with a detailed discussion of strategies for alleviating the foreign body response (FBR) and abnormalities seen at the interface of MEAs and the brain tissue following MEA implantation. Various surface modifications, including natural/synthetic surface coatings, hydrogels, and topography alterations, have shown to be highly successful in improving neural cell adhesion, reducing gliosis, and increasing MEA longevity. Different MEA surface geometries, such as those seen in the Utah and Michigan arrays, can help alleviate the resultant FBR by reducing insertion damage, while providing new avenues for improving MEA recording performance and resolution. Increasing overall flexibility of MEAs as well as reducing their stiffness is also shown to reduce MEA induced micromotion along with FBR severity. By combining multiple different properties into a single MEA, the severity and duration of an FBR postimplantation can be reduced substantially. Abstract : This paper provides an overview of neural interface systems and their applications, along with a detailed discussion of strategies for alleviating the foreign body response and abnormalities seen at the interface of microelectrode array (MEA) and the brain tissue following the MEA implantation.